Strategi Konten Media Sosial dalam Meningkatkan Daya Tarik Perpustakaan dan Galeri Kota Bogor - Risdalia Putri; Christian Wiradendi Wolor; Adnan Kasofi (Politeknik Kampar, 2025)
The purpose of this study is to comprehend how Perpustakaan dan Galeri Kota Bogor use sosial media, including how well it reaches the publik, what kinds of content it delivers, and the difficulties in managing it. The study uses a qualitative methodology that includes sosial media content documentation, interviews, and observation. The findings show that, albeit not always and without a planned content strategy, Instagram and TikTok have been utilized for marketing and education. Lack of a content plan, content calendar, and content pillars are among the main obstacles, as are insufficient facilities and human resources. Consequently, better sosial media management skills and a more systematic approach to content planning are required.